Fashion Sebagai Komunikasi Identitas Sub Budaya (Kajian Fenomenologis terhadap Komunitas Street Punk Semarang) - Dominikus Isak Petrus Berek (Interaksi: Jurnal Ilmu Komunikasi, 2014)
What are the things that disclosed the identity of Street Punk fashion? and what kind of communication is represented Street Punk through fashion? If identity becomes ambiguous Punk by rogue elements who identified himself as a Punk , then there differences in identity between Punk Street Punk and other communities through fashion? In this study fashion as communication with a phenomenological approach, researchers introduce fashion as a way of communicating the identity of a sub culture that exists in our midst. Taking of theoretical approaches to communication and culture, in particular the approach of Malcolm Bernard (1995) and friend’s, the author then examines the consequences of communication as identity. The types of identities that observed in everyday life and to a certain statement, may be refuted by ordinary people with common sense, then by researchers in the context of this study, the types of identities that can be observed by the researchers and verified in the experience of the subject scientific.